Transformations of Social-Ecological Systems Studies in Co-creating Integrated Knowledge Toward Sustainable Futures (Ecological Research Monographs,, 2018)
Through this book, readers will gain a comprehensive overview of transdisciplinary knowledge co-production in local contexts as an issue-driven and solution-oriented process, and will come to understand its relationship to societal transformation processes toward sustainability. In a single volume, the theory, approaches and academic implications of this novel type of knowledge production are addressed, together with its societal impacts. In the midst of global anthropogenic impacts that affect various environments, over the past few decades we have observed autonomous initiatives in local communities around the world to tackle these environmental challenges. It is vital that such local actions be scaled up to achieve sustainable societies, which requires societal transformation on larger scales. Thanks to numerous collaborative actions in local communities, transdisciplinary knowledge co-production among diverse stakeholders has successfully been mobilized, resulting in the development of Integrated Local Environmental Knowledge (ILEK); knowledge that can inform and support decisions and actions promoting the sustainable transformation of society. This book uses comparative case studies in communities around the world to illuminate and clarify processes and factors promoting the co-production and utilization of ILEK to facilitate decision-making. In addition, readers will gain deeper insights into the science-society interactions that can contribute to finding collaborative solutions to a wide range of critical environmental problems. Though the book is ideally suited for researchers and students, it also offers a valuable resource for practitioners, government agencies, and stakeholder agencies.